KORELASI PERKULIAHAN BERBASIS E-LEARNING TERHADAP MOTIVASI BELAJAR MAHASISWA PENDIDIKAN MATEMATIKA UNIVERSITAS PANCASAKTI MAKASSAR - Muthmainnah Asmal (Nusantara Hasana Berdikari, 2022)
The purpose of this study was to determine whether there is a correlation between e-learning-based lectures and student motivation for Mathematics Education, Pancasakti University Makassar. This study uses a quantitative approach with the correlational method. The sample determination is carried out using the Non Probability Sampling type with the saturated sampling technique. The samples taken are all 28 students of Mathematics Education Class 2021. The data collection techniques used are: 1) Questionnaires related to e-learning based lectures learning, and 2) Student learning motivation questionnaire. Data analysis used correlation analysis with rcount = 0.550 and rtable = 0.31. Because the value of rcount is greater than the price of rtable, Ho is rejected and Ha is accepted. So it can be concluded that there is a positive and significant effect of e-learning-based lectures on the learning motivation of mathematics education students.